Calcium sulfate whisker-cellulose fiber concrete, preparation method and product thereof
By using calcium sulfate whiskers and cellulose fibers as reinforcement materials in concrete, the problem of poor mechanical properties of existing concrete after high temperatures is solved, which significantly improves compressive strength and chloride ion permeability, and improves the overall durability of concrete. performance.
Patent Information
- Application Number
- CN202411626524.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
Existing concrete has poor mechanical properties, poor chloride ion permeability, carbonization resistance, and difficulty in reinforcing and repairing.
Using calcium sulfate whiskers and cellulose fibers as reinforcement materials, the high temperature stability of calcium sulfate whiskers and cellulose fibers are used to improve the high temperature stability of calcium sulfate whiskers and the good hydrophilicity and tensile strength of cellulose fibers. Structural properties of concrete.
It significantly improves the compressive strength and tensile strength of concrete after high temperature, reduces the chloride ion permeability coefficient and carbonization coefficient, and improves the durability of concrete.
Smart Images

Figure CN119430764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a calcium sulfate whisker-cellulose fiber concrete, a preparation method and a product thereof. Background Art
[0002] Concrete is an indispensable building material for modern construction. Ordinary concrete has the advantages of easy material acquisition, strong plasticity, and high compressive strength, but it also has disadvantages such as low tensile strength, easy cracking, and poor mechanical properties after high temperature. In addition, concrete reinforcement and repair are difficult, and once problems occur, they are difficult to repair. Ordinary concrete has poor mechanical properties after high temperature, resistance to chloride ion penetration, and resistance to carbonization (poor pore structure); calcium sulfate whiskers are only used for cement-based materials to resist high temperatures, and fail to solve the problem of high temperature resistance at the concrete level.
[0003] Whiskers and fibers can inhibit the expansion of cracks inside concrete at different scales, reduce the porosity of concrete, and improve the comprehensive performance of concrete structures. Cellulose fiber is an environmentally friendly fiber derived from natural plants. It has good hydrophilicity and high tensile strength. It has a low melting point and can be completely melted at a high temperature of about 400°C. Adding cellulose fiber can reduce shrinkage cracks inside concrete, leave a melting channel inside the concrete when it is subjected to high temperature, release pore water pressure, and effectively prevent concrete from spalling. When cellulose fiber is applied to concrete, it can effectively improve the durability of concrete, such as impermeability, chloride ion permeability, and carbonization resistance; calcium sulfate whiskers, as an industrial by-product, have high mechanical properties and high temperature stability, which can effectively improve the mechanical properties, chloride ion permeability, and frost resistance of concrete, and greatly improve the mechanical properties of cement-based materials after high temperature. Summary of the invention
[0004] In order to solve the problems of the prior art, the present invention provides a calcium sulfate whisker-cellulose fiber concrete, a preparation method and a product thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A calcium sulfate whisker-cellulose fiber concrete, comprising cellulose fibers; the concrete also comprises: calcium sulfate whiskers, wherein the mass content of the calcium sulfate whiskers is 1.5-2.5%, the length is set between 50 and 200 μm, and the diameter is set between 1 and 5 μm; The amount of cellulose fiber is 0.85-0.95 kg / m 3 The length is set at about 2~3mm, and the diameter is set at about 15~20μm.
[0006] The mass content of the calcium sulfate whisker is 2%, the length is set between 50 and 200 μm, and the diameter is set between 1 and 5 μm; The amount of cellulose fiber is 0.9 kg / m 3 , the length is set at about 2~3mm, and the diameter is set at about 15~20μm.
[0007] The calcium sulfate whisker-cellulose fiber concrete further comprises aggregate, cementitious material and water reducing agent; the aggregate comprises coarse aggregate and fine aggregate.
[0008] The calcium sulfate whisker-cellulose fiber concrete, the water reducer includes a polycarboxylic acid water reducer, a naphthalene water reducer, a wood calcium water reducer or a composite water reducer.
[0009] The preparation method of the calcium sulfate whisker-cellulose fiber concrete comprises the following steps: (a) mixing the coarse aggregate and the pre-soaked cellulose fibers uniformly to obtain a mixture; (b) adding fine aggregate and stirring evenly, then adding cement and stirring evenly, then adding calcium sulfate whisker and stirring evenly, adding water and water reducing agent into the mixture and stirring evenly, thereby obtaining calcium sulfate whisker-cellulose fiber concrete.
[0010] The preparation method comprises the following steps: (a) dry-mixing the coarse aggregate and the pre-soaked cellulose fibers for 2 minutes and stirring evenly to obtain a mixture; (b) Add fine aggregate to the mixture and dry mix for 30 seconds, then add cement and continue stirring for 1 minute, add calcium sulfate whiskers and stir for 2 minutes, and finally add water and water reducing agent to the mixture and stir for 3 minutes to obtain calcium sulfate whisker-cellulose fiber concrete.
[0011] The preparation method further comprises the following steps: The newly mixed concrete is quickly loaded into a test mold that has been pre-brushed with a release agent, placed on a vibration table for vibration to make it dense, and the surface of the specimen is smoothed with a spatula and cured to obtain a calcium sulfate whisker-cellulose fiber concrete product.
[0012] A calcium sulfate whisker-cellulose fiber concrete product is prepared by the preparation method described in claim 7.
[0013] Compared with the prior art, the beneficial effect of the invention is that the calcium sulfate whisker-cellulose fiber concrete disclosed by the present invention has good compatibility with concrete in both fiber sizes. Calcium sulfate whiskers, as sub-nanoscale fibers, give full play to their size effect, physical filling effect and fiber characteristics, and calcium sulfate whiskers can participate in cement hydration reaction to generate calcium aluminate, further optimize the pore structure of concrete, and improve the concrete's resistance to chloride ion permeability and carbonization. From the perspective of the mechanism of multi-scale fiber-reinforced concrete, in the crack development stage of concrete, whiskers and fibers inhibit the development of cracks from the microscopic and macroscopic scales respectively, and exert a positive mixing effect to strengthen concrete at different stress stages, thereby enhancing the performance of concrete. The high-temperature compressive strength and splitting tensile strength of calcium sulfate whisker-cellulose fiber concrete are significantly higher than those of ordinary concrete, and the chloride ion permeability coefficient and carbonization coefficient below 400°C are significantly lower than those of ordinary concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Other features, objectives and advantages of the present invention will become more apparent from a reading of the detailed description of non-limiting embodiments made with reference to the following accompanying drawings.
[0015] Figure 1 It is a schematic diagram of the cellulose fiber structure of the present invention.
[0016] Figure 2 It is a schematic diagram of the structure of calcium sulfate whiskers in the present invention.
[0017] Figure 3 The invention discloses a construction process flow chart of calcium sulfate whisker-cellulose fiber concrete.
[0018] Figure 4 It is a schematic diagram of the microscopic morphology of cellulose fibers in the present invention.
[0019] Figure 5 It is a schematic diagram of the microscopic morphology (×8000) of the calcium sulfate whisker of the present invention.
[0020] in Figure 4 (a) shows that the surface of cellulose fiber is rough, which is the basis for its close bonding with concrete. There are cellulose fibers pulled out on the failure surface of concrete, indicating that cellulose fibers consume crack energy through pulling out. Since cellulose fibers have low tensile strength and short length, they cannot effectively limit the development of macroscopic cracks in concrete. Therefore, cellulose fibers have little effect on improving the mechanical properties of concrete. Figure 4 (b) The internal hollow structure of cellulose fibers can be clearly observed. This structure is equivalent to a small "water reservoir", which can effectively prevent the occurrence of concrete bleeding and is also conducive to the long-term hydration reaction of cement.
[0021] Figure 5The results show that calcium sulfate whiskers reduce the porosity of concrete by filling it with their own materials, and participate in the cement hydration reaction to generate calcium vanadium to fill the pores of concrete, making it denser. At the same time, calcium sulfate whiskers are coated with hydrated calcium silicate, so that calcium sulfate whiskers form a good bonding force with the concrete matrix, thereby limiting the development of micro cracks inside the concrete. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below by examples, which are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0023] A calcium sulfate whisker-cellulose fiber concrete, comprising cellulose fibers; the concrete also comprises: calcium sulfate whiskers, wherein the mass content of the calcium sulfate whiskers is 1.5-2.5%, the length is set between 50 and 200 μm, and the diameter is set between 1 and 5 μm; The amount of cellulose fiber is 0.85-0.95 kg / m 3 The length is set at about 2~3mm, and the diameter is set at about 15~20μm.
[0024] The mass content of the calcium sulfate whisker is 2%, the length is set between 50 and 200 μm, and the diameter is set between 1 and 5 μm; The amount of cellulose fiber is 0.9 kg / m 3 , the length is set at about 2~3mm, and the diameter is set at about 15~20μm.
[0025] The calcium sulfate whisker-cellulose fiber concrete further comprises aggregate, cementitious material and water reducing agent; the aggregate comprises coarse aggregate and fine aggregate.
[0026] The calcium sulfate whisker-cellulose fiber concrete, the water reducer includes a polycarboxylic acid water reducer, a naphthalene water reducer, a wood calcium water reducer or a composite water reducer.
[0027] The preparation method of the calcium sulfate whisker-cellulose fiber concrete comprises the following steps: (a) mixing the coarse aggregate and the pre-soaked cellulose fibers uniformly to obtain a mixture; (b) adding fine aggregate and stirring evenly, then adding cement and stirring evenly, then adding calcium sulfate whisker and stirring evenly, adding water and water reducing agent into the mixture and stirring evenly, thereby obtaining calcium sulfate whisker-cellulose fiber concrete.
[0028] The preparation method comprises the following steps: (a) dry-mixing the coarse aggregate and the pre-soaked cellulose fibers for 2 minutes and stirring evenly to obtain a mixture; (b) Add fine aggregate to the mixture and dry mix for 30 seconds, then add cement and continue stirring for 1 minute, add calcium sulfate whiskers and stir for 2 minutes, and finally add water and water reducing agent to the mixture and stir for 3 minutes to obtain calcium sulfate whisker-cellulose fiber concrete.
[0029] The preparation method further comprises the following steps: The newly mixed concrete is quickly loaded into a test mold that has been pre-brushed with a release agent, placed on a vibration table for vibration to make it dense, and the surface of the specimen is smoothed with a spatula and cured to obtain a calcium sulfate whisker-cellulose fiber concrete product.
[0030] A calcium sulfate whisker-cellulose fiber concrete product is prepared by the preparation method described in claim 7.
[0031] Embodiment 1: This Example 1 is an exemplary comparison of the cube compressive strength of calcium sulfate whisker-cellulose fiber concrete after high temperature.
[0032] The ingredients and components of concrete are: water-cement ratio is 0.47, cement strength is 42.5, and other mix proportions are shown in Table 6 Concrete mix proportions.
[0033] The size of the cube test block used in this embodiment is a specimen of 100mm×100mm×100mm. Five temperature conditions (25℃, 200℃, 400℃, 600℃, 800℃) were set, and the heating rate was 10℃ / min. After reaching the target temperature, the temperature was kept constant for three hours, and the high-temperature cube compression test was performed on the test block after high temperature. There were three test pieces in each group, and a total of 10 groups of experiments were conducted. The components of each group of experiments are shown in Table 7, which is a list of components of the high-temperature cube compressive strength test of Example 1.
[0034] PC is a control experiment, and the content of calcium sulfate whisker and cellulose fiber is 0. The other group is calcium sulfate whisker-cellulose fiber concrete. The table lists the percentage of calcium sulfate whisker in cement mass, cellulose fiber content, and the compressive strength of calcium sulfate whisker-cellulose fiber concrete test blocks after high temperature and the growth rate of compressive strength after high temperature.
[0035] It can be seen from the test data that the compressive strength of the calcium sulfate whisker-cellulose fiber concrete disclosed in the embodiment of the present invention increases with a high growth rate, and the compressive strength is improved after high temperature compared with ordinary concrete, with the maximum improvement rate of 11.6%.
[0036] Embodiment 2: This Example 2 is an exemplary comparison of the post-high-temperature splitting tensile strength of calcium sulfate whisker-cellulose fiber concrete.
[0037] The concrete base mix ratio is the same as that in Example 1.
[0038] The size of the splitting tensile test block used in this embodiment is a specimen of 100mm×100mm×100mm. The temperature conditions and heating program are the same as those in Example 1. The high-temperature splitting tensile test is performed on the test block after high temperature. There are three test pieces in each group, and a total of 10 groups of experiments are performed. The components of each group of experiments are shown in Table 8. Table 8 List of components of the cube splitting tensile strength test after high temperature in Example 2
[0039] PC is a control experiment, and the dosage of calcium sulfate whisker and cellulose fiber is 0. The other group is calcium sulfate whisker-cellulose fiber concrete. The table lists the percentage of calcium sulfate whisker in cement mass, cellulose fiber dosage, and the splitting tensile strength of calcium sulfate whisker-cellulose fiber concrete test block after high temperature and the growth rate of splitting tensile strength after high temperature.
[0040] It can be seen from the test data that the splitting tensile strength of the calcium sulfate whisker-cellulose fiber concrete disclosed in the embodiment of the present invention is increased, and the splitting tensile strength after high temperature action of 800° C. is 20.5% higher than that of ordinary concrete.
[0041] Embodiment 3: This Example 3 is an exemplary comparison of the chloride ion penetration resistance of calcium sulfate whisker-cellulose fiber concrete after high temperature.
[0042] The concrete base mix ratio is the same as that in Example 1.
[0043] The chloride ion penetration resistance test piece used in this embodiment is a cylindrical test piece of Φ100mm×50mm. The temperature conditions and heating program are the same as those in Example 1. The test piece after high temperature is subjected to the chloride ion penetration test. Three test pieces are in each group, and a total of 10 groups of experiments are conducted. The components of each group of experiments are shown in Table 9. Table 9 List of components of the chloride ion diffusion coefficient experiment after high temperature in Example 3
[0044] PC is a control experiment, and the dosage of calcium sulfate whisker and cellulose fiber is 0. The other group is calcium sulfate whisker-cellulose fiber concrete. The table lists the percentage of calcium sulfate whisker in cement mass, cellulose fiber dosage, and the chloride ion diffusion coefficient of the calcium sulfate whisker-cellulose fiber concrete test block after high temperature and the reduction rate of the chloride ion diffusion coefficient after high temperature.
[0045] It can be seen from the test data that the chloride ion diffusion coefficient of the calcium sulfate whisker-cellulose fiber concrete disclosed in the embodiment of the present invention at 400° C. and below is reduced, with the maximum reduction rate being 25.0%.
[0046] Embodiment 4: This Example 4 is an exemplary comparison of the carbonation resistance of calcium sulfate whisker-cellulose fiber concrete after high temperature.
[0047] The concrete base mix ratio is the same as that in Example 1.
[0048] The size of the carbonization test block used in this embodiment is a test piece of 100mm×100mm×400mm. The temperature conditions and heating program are the same as those in Example 1. The test piece after high temperature is subjected to carbonization test. There are three test pieces in each group, and a total of 10 groups of experiments are carried out. The components of each group of experiments are shown in Table 10.
[0049] PC is a control experiment, and the content of calcium sulfate whisker and cellulose fiber is 0. The other group is calcium sulfate whisker-cellulose fiber concrete. The table lists the percentage of calcium sulfate whisker in cement mass, cellulose fiber content, and the carbonization coefficient of calcium sulfate whisker-cellulose fiber concrete test block after high temperature and the reduction rate of carbonization coefficient after high temperature.
[0050] It can be seen from the test data that the chloride ion diffusion carbonization coefficient of the calcium sulfate whisker-cellulose fiber concrete disclosed in the embodiment of the present invention at 400°C and below is reduced, with the maximum reduction rate being 10.7%.
[0051] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A calcium sulfate whisker-cellulose fiber concrete, comprising cellulose fibers; characterized in that: The concrete also includes: calcium sulfate whiskers, wherein the mass content of the calcium sulfate whiskers is 1.5-2.5%, the length is set at 50-200 μm, and the diameter is set at 1-5 μm; The amount of cellulose fiber is 0.85-0.95 kg / m 3 , the length is set at 2~3mm, and the diameter is set at 15~20μm.
2. The calcium sulfate whisker-cellulose fiber concrete according to claim 1, characterized in that: The mass content of the calcium sulfate whisker is 2%, the length is set at 50 to 200 μm, and the diameter is set at 1 to 5 μm; The amount of cellulose fiber is 0.9 kg / m 3 , the length is set at 2~3mm, and the diameter is set at 15~20μm.
3. The calcium sulfate whisker-cellulose fiber concrete according to claim 2, characterized in that: The concrete also includes aggregate, cementitious material and water reducing agent; the aggregate includes coarse aggregate and fine aggregate.
4. The calcium sulfate whisker-cellulose fiber concrete according to claim 3, characterized in that: The water reducer includes a polycarboxylic acid water reducer, a naphthalene water reducer, a wood calcium water reducer or a composite water reducer.
5. The method for preparing calcium sulfate whisker-cellulose fiber concrete according to claim 4, characterized in that: The following steps are involved: (a) mixing the coarse aggregate and the pre-soaked cellulose fibers uniformly to obtain a mixture; (b) adding fine aggregate and stirring evenly, then adding cement and stirring evenly, then adding calcium sulfate whisker and stirring evenly, adding water and water reducing agent into the mixture and stirring evenly, thereby obtaining calcium sulfate whisker-cellulose fiber concrete.
6. The method for preparing calcium sulfate whisker-cellulose fiber concrete according to claim 5, characterized in that: The following steps are involved: (a) dry-mixing the coarse aggregate and the pre-soaked cellulose fibers for 2 minutes and stirring evenly to obtain a mixture; (b) Add fine aggregate to the mixture and dry mix for 30 seconds, then add cement and continue stirring for 1 minute, add calcium sulfate whiskers and stir for 2 minutes, and finally add water and water reducing agent to the mixture and stir for 3 minutes to obtain calcium sulfate whisker-cellulose fiber concrete.
7. The method for preparing calcium sulfate whisker-cellulose fiber concrete according to claim 6, characterized in that: The following steps are also included: The newly mixed concrete is quickly loaded into a test mold that has been pre-brushed with a release agent, placed on a vibration table for vibration to make it dense, and the surface of the specimen is leveled with a spatula and cured to obtain a calcium sulfate whisker-cellulose fiber concrete product.
8. A calcium sulfate whisker-cellulose fiber concrete product prepared by the preparation method according to claim 7.